Feasibility study on the development of an academic thesis source code database in the University of the Philippines-Diliman - Villamin, Redelyn P. (Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Technology, in its fast pace in terms of advancement, generates the great need in research to usher further and more powerful developments. Related fields to technology, such as the dynamic software engineering and design, require the process of research. However, a significant research will not be possible without the reliable sources and references to start with. In terms of software source code repositories, the Internet is probably the most sought reference for students. However, with all the massive information located in the Internet, how can one be so sure that the obtained information is significant, consistent and came from trusted sources?